Deploying business excellence – success factors for high performance. Issue 2 (1st February 2016) - Tickle, Matthew; Mann, Robin; Adebanjo, Dotun
Abstract : Purpose: – The purpose of this paper is to improve the understanding of how organisations successfully deploy business excellence (BE) by comparing the tools and strategies implemented by organisations at different levels of BE maturity. Design/methodology/approach: – The study used a combination of a questionnaire, discussion groups and interviews with respondents including private sector organisations across India, Japan, Republic of China, Singapore and Thailand. These countries were selected due to them being considered as having the most advanced BE organisations in Asia by the Asian Productivity Organisation (APO) that commissioned the study. Once triangulated, the quantitative data were analysed through use of the IBM SPSS Statistical software package. Findings: – The study has shown that on average, organisations with higher BE maturity outperform their less mature counterparts. The study also revealed that organisations with a high BE maturity were more likely to use specific tools and were more likely to use some of these tools more effectively. Finally, the study identified differences in strategic approaches to BE between organisations with high and low BE maturity. Research limitations/implications: – Only five Asian countries were considered due to resource limitations. However, the study of 74 organisations represents one of the most comprehensive to date with 30 of these organisations being award winners. Practical implications: – The findings offer guidance to those organisations wishing to progress from a low level of BE maturity to a more advanced level. The findings have already assisted the APO and its 20 member countries in the development and implementation of strategic interventions at a regional and national level. Originality/value: – No other study in Asia has been conducted on such a large sample of BE-orientated organisations. The study was also unique in its focus on the tools and strategies that should be used for successful BE deployment. In addition, the study is one of only a few in Asia that has studied the results of BE on organisational performance.